On the Optimal Convergence Rate of a Robin-Robin Domain Decomposition Method (Journal of Computational Mathematics, 2018)
In this work, we solve a long-standing open problem: Is it true that the convergence rate of the Lions' Robin-Robin nonoverlapping domain decomposition (DD) method can be constant, independent of the mesh size $h?$ We closed this old problem with a positive answer. Our theory is also verified by numerical tests.